2013
DOI: 10.1016/j.freeradbiomed.2013.05.012
|View full text |Cite
|
Sign up to set email alerts
|

One-electron oxidation and reduction of glycosaminoglycan chloramides: A kinetic study

Abstract: Hypochlorous acid and its acid-base counterpart, hypochlorite ions, produced in inflammatory conditions, may produce chloramides of glycosaminoglycans, the latter being significant components of the extracellular matrix (ECM). This may occur through the binding of myeloperoxidase directly to the glycosaminoglycans.The N-Cl group in the chloramides is a potential selective target for both reducing and oxidising radicals, leading possibly to more efficient and damaging fragmentation of these biopolymers relative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 59 publications
2
16
0
Order By: Relevance
“…This was supported by the lack of any demonstrable reaction of these species with the parent molecule, HA, and also by the absorption spectra of transient species attributable to carbon-centred free radicals formed on the glucosamine moiety [41]. The latter observation provided support for the 1,2 hydrogen shift mechanism for HACl proposed by Davies and co-workers as shown in Scheme 2 in which a chloride ion is eliminated by one-electron reductants to form a nitrogen-centred radical in the first instance followed by rapid re-arrangement to produce the C-2 radical on the glucosamine moiety and/or C-4 radicals on the uronic acid moiety [22].…”
Section: Resultsmentioning
confidence: 84%
See 2 more Smart Citations
“…This was supported by the lack of any demonstrable reaction of these species with the parent molecule, HA, and also by the absorption spectra of transient species attributable to carbon-centred free radicals formed on the glucosamine moiety [41]. The latter observation provided support for the 1,2 hydrogen shift mechanism for HACl proposed by Davies and co-workers as shown in Scheme 2 in which a chloride ion is eliminated by one-electron reductants to form a nitrogen-centred radical in the first instance followed by rapid re-arrangement to produce the C-2 radical on the glucosamine moiety and/or C-4 radicals on the uronic acid moiety [22].…”
Section: Resultsmentioning
confidence: 84%
“…However, evidence from time-resolved studies appears to support the formation of C-2 radicals since the transient spectra observed are consistent with those expected for carbon-centred radicals associated with an adjacent nitrogen atom such as RCONRCH 2 . (where R can be H-or CH 3 -) [41]. It seems probable therefore that the 100% fragmentation yield observed for HACl occurs via the C-2 radical on the glucosamine moiety with the subsequent β-scission being 100% effective.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Hence, for the more biologically relevant carbonate radical, a much higher degree of selectivity of attack with glycosaminoglycans is to be expected, as confirmed in fragmentation studies (Sibanda et al 2013a). The reactivities of both oxidizing and strongly reducing radicals with the chloramide derivatives of hyaluronan and heparin were investigated using both pulse radiolysis and laser flash photolysis techniques (Sibanda et al 2013b). The strong reducing agent, the formate radical was produced by both pulse radiolysis and by laser flash photolysis.…”
Section: Pulse Radiolysis and Laser Flash Photolysismentioning
confidence: 99%
“…[33][34][35][36][37][38][39][40] Due to its outstanding oxidative power, this species can significantly alter the activities and availabilities of biomolecules.…”
Section: Introductionmentioning
confidence: 99%